Digital Transformation in Hospital Administration: Improving Data Management and Reducing Paper-Based Processes - Abdulrahman Mahbub Alotaibi; Khaled Raja Al Harithi; Abdul Moein Musaed AlQarni; Hussam Mohammed Alsahafi; Alaa Ibrahim Alghanmi; Ahmed Saeed Alahmadi; Abdullah Saleh Alzebali; Naji Suyayfl Mubarak Aljohani; Mansour Mohammed Alghamdi (International Journal of Medical Toxicology and Legal Medicine, 2024)
This paper explores the changes which have taken place in hospital administration through the use of information technology especially in the management of data and reduction of paperwork. Qualitative in nature and mainly employing secondary data, a thematic analysis is used to examine trends, issues, and resultant effects of previous literature, case studies, and industry reports. Some of the important themes that emerged are improvements in the efficiency, improvements in accuracy of the data, reduction of costs and some of the challenges faced are the cost of implementation and issue of staff opposition. Consequently, the study shows that digital tools greatly enhance the work of hospitals, although the effective implementation of technology entails effective planning and management of stakeholders. In conclusion the paper gives potential implication of the use of innovation in the management of health care organizations.